Respostas

A melhor resposta!
2014-05-20T09:28:41-03:00
1)9a²+12ab+4b²

2)a²-2ab+b²

3)16x²-24xy+9y²
2 5 2
2014-05-20T10:00:41-03:00
Pela Propriedade distribuitiva teremos:
1-(3a+2b)²= (3a+2b)(3a+2b)= (3a.3a)+(3a.2b)+(2b.3a)+(2b.2b)
                                       =9a
²+6ab+6ab+4b²
                                       = 9a²+12ab+4b²

2-(a-b)²= (a-b)(a-b)= (a.a)-(a.b)-(b.a)+(b.b)
                                       =a²-ab-ab+b²
                                       = a²-2ab+b²

3-(4x-3y)²= (4x-3y)(4x-3y)= (4x.4x)-(4x.3y)-(3y.4x)+(3y.3y)
                                       =16x²-12xy-12xy+9y²
                                       = 16x²-24xy+9y²